Metode Pendidikan Agama Islam dalam Perspektif Al-Quran dan Hadist - Leman, Suwanggi; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Methodology is a crucial component in determining the success or failure of an education. This allows learning material to be taught effectively and efficiently to students. To achieve this, teachers should use a multi-strategy and multi-sector approach, including motivational and pedagogical approaches. This research uses qualitative methods, such as library research, to explore Islamic education methods. The methodology must take into account the individual or social aspects of the students and teachers themselves. The three components of Islamic education include knowledge, skills, and knowledge. Understanding methodology is critical to determining educational effectiveness. In the world of Islamic religious education, the process and goals of education should be in accordance with the Koran and Hadith as the main sources of Islamic teachings. In these two sources of law there must be a strong foundation regarding educational methods, as implemented by the Prophet Muhammad in preaching and educating Muslims. The results show that there are five educational methods in the Koran and Hadith.